Nayika sculptures on the walls of the Harshnath Temple - Temples of India Project Team (Jio Institute, 2024)
Adorning the walls within the sanctum of the Harshnath Temple are exquisite sculptures of nayikas. Most of them are inscribed with epithets of the 10th century CE Kutila script.